Field-induced charge-density-wave transitions in the organic metal α-(BEDT-TTF)2KHg(SCN)4 under pressure: Органические проводники - Andres, D.; Kartsovnik, M.V.; Biberacher, W.; Neumaier, K.; Sheikin, I.; Müller, H.; Kushch, N.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Successive magnetic-field-induced charge-density-wave transitions in the layered molecular conductor α-(BEDT-TTF)2KHg(SCN)4 are studied in the hydrostatic pressure regime, in which the zero field chargedensity- wave (CDW) state is completely suppressed. The orbital effect of the magnetic field is demonstrated to restore the density wave, while the orbital quantization induces transitions between different CDW states at changing the field strength. The latter appear as distinct anomalies in the magnetoresistance as a function of field. The interplay between the orbital and Pauli paramagnetic effects acting, respectively, to enhance and to suppress the CDW instability is particularly manifest in the angular dependence of the field-induced anomalies.